"Road Safety Sequence" - A New Concept of the Road Safety Management in Poland - Andrzej Szymanek (Communications - Scientific letters of the University of Zilina, 2021)
The article shows a fragment of the results of the author’s concept of road safety management in Poland. The article shows the “program sequence” of the construction action of road safety management system in Poland. The main component of this "sequence" of actions to improve the road safety - should be the "road risk management model". It should be widely used in Poland as an element of knowledge and practices of international road safety management. It is primarily about the model of the Office for Land Transport Safety Authority in New Zealand adopted by the EU in its road safety policy. The article also presents other components of the author’s concept, including the "3 levels" model of risk management, the idea of which is to isolate three categories of the risk associated with any transport system.